(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
NF-KB (nuclear factor kappa-light-chain-enhancer of activated B cells) is a collective name for the complexes formed by five NF-KB-Rel family members which control transcription of DNA. NF-KB1 (p50) is a member of NF-KB protein family which is known to regulate a wide range of genes those are involved in various physiological processes viz. immune and inflammatory responses, apoptosis, stress, cell proliferation and developmental process. This review is based on the detail bioinformatic analysis of NF-KB1 regulation on microRNA. Basically the miRNAs are small non-coding RNA shown to be involved in many biological and cellular processes. The NF-KB1 as a transcription factor regulates 29 microRNA genes by binding to its promoter region. Most of these microRNAs are associated with various types of cancers, including lung, prostate, breast and gastrointestinal cancer.